Existing and Proposed Urban Geosites Values Resulting from Geodiversity of Poznań City - Zwoliński Zbigniew; Hildebrandt-Radke Iwona; Mazurek Małgorzata; Makohonienko Mirosław (Quaestiones Geographicae, 2017)
Poznań, a city in central-western Poland, is located in the lowland region but has no less attractive geomorphological and human history. It was here that Poland was born at the end of the tenth century. The city’s location is connected with the meridian course of the Warta River valley. In contrast, in the northern part of the city, there is a vast area of the frontal moraines of the Poznań Phase of the Weichselian Glaciation. Against the backdrop of the geomorphological development of the city, the article presents the existing geosites, classified as urban geosites. The present geosites include three lapidaries with Scandinavian postglacial erratics, one of them also with stoneware, a fragment of a frontal push moraine and impact craters. Besides, three locations of proposed geosites with rich geomorphological and/or human history were identified. These are as follows: the peat bog located in the northern part of the city, defence ramparts as exhumed anthropogenic forms, and the Warta River valley. The existing and proposed geosites in Poznań were evaluated in three ways. In general, it should be assumed that the proposed new geosites are higher ranked than the current ones.